Translating healthcare innovation from academia to industry. (March 2017) - Sanami, Mohammad; Flood, Tim; Hall, Richard; Kingscott, Fiona; Jayne, David; Culmer, Peter
Innovation lies at the heart of academia, and universities generate high-quality, intellectual property on a large scale. However, commercial translation of this intellectual property has traditionally been poor, particularly in the critical healthcare sector. It is critical that this situation is addressed to ensure that innovation from research institutes can fulfil its potential and progress to have a genuine impact on the outside world. In this article, we consider the nature of healthcare innovation in academia and ways in which commercial translation of intellectual property can be successfully realised. This is first analysed from an academic perspective, with a particular focus on how academic motivations and work practices can shape successful translation. We then switch perspective to examine the same process from an industry perspective, looking at the characteristics and expectations involved in the innovation life cycle. To place these analyses in context, we present a case study examining a project being undertaken to commercialise a novel surgical instrument, the intra-abdominal platform, from identification of clinical need, through the development life cycle, to commercialisation of the system. We reflect on the successes and challenges encountered during the intra-abdominal platform project, the broader lessons learned and in conclusion use these to emphasise how academia can adopt practices to better translate intellectual property in the future.